KISAH HAGAR DAN ISMAEL SEBAGAI “TEROWONGAN SILATURAHMI”: DASAR BIBLIS MELAWAN ANTI PERADABAN - Servinus Haryanto Nahak (Jurnal Pelayanan Pastoral, 2024)
This article discusses the story of the expulsion of Hagar and Ishmael according to the Book of Genesis. The negative profile of Hagar and Ishmael as inherited in the New Testament (cf. Galatians 4:22-26) needs to be balanced with a more positive model of interpretation. Using qualitative methods through document research, the author emphasizes the opinion that the Book of Genesis is a result of editorial work that intentionally seeks a path of dialogue between different tribes in Palestine. To support the framework above, the author uses narrative analysis and evidence from redaction criticism. The results of this study showed: firstly, the figures of Hagar and Ishmael according to the Book of Genesis are not always black and white as Paul describes in Galatians. Secondly, the story of Hagar and Ishmael is a form of negotiation or joint consensus to seek dialogue and a path of peace so that it can be used as a biblical basis for discussions on interfaith dialogue or borrowing the term after Pope Francis' visit: “the silaturahmi tunnel”.